Virtual Dig: A Simulated Archaeological Excavation of a Middle Palaeolithic Site in France by H.L. Dibble, S.P. McPherron and B.J. Roth - Richard Osgood (Internet Archaeology, 2002)
This book/CD-Rom publication seems intended to enhance the 'method and theory' segment in many undergraduate archaeology degrees, to escape from traditional drawings of sections and information on various digging styles. As such it is a bold move, especially when budgetary considerations also feature writ large in the planning - as indeed they must on all real excavations.